ERROR ANALYSIS ON STUDENTS' WRITINGS (A case study of General English Students of Intensive English Course Semarang) - Setyo Prasiyanto Cahyono (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2009)
this study aims at describing the linguistics errors that appears in the students' writings and discovering kinds of error the students made in their writings. The subject of this research is taken from the students' writings made by the fourth level students of General English of Intensive English Course Semarang. The result of the data reveals that all the students made some errors in their writings. The types of error the students made are developmental, interlingual, ambiguous or other errors. Developmental errors are errors similar to those made by the students learning the target language as their first language. Then, interlingual errors are similar in structure to a semantically equivalent phrase or sentence in the learner's native language. Meanwhile, ambiguous errors are those that could be classified equally well as developmental or interlingual.Key words: error, developmental, interlingual, ambiguous